Factors affecting poly(3-hydroxybutyrate) production from oil palm frond juice by cupriavidus necator (CCUG52238 T) - Mior Ahmad Khushairi, Mohd Zahari; Hidayah, Ariffin; Mohd Noriznan, Mokhtar; Jailani, Salihon; Shirai, Yoshihito; Mohd Ali, Hassan (Hindawi Publishing Corporation, 2012)
Factors influencing poly(3-hydroxybutyrate) P(3HB) production by  Cupriavidus necator  C C U G 5 2 2 3 8T utilizing oil palm frond (OPF) juice were clarified in this study. Effects of initial medium pH, agitation speed, and ammonium sulfate (NH4)2SO4 concentration on the production of P(3HB) were investigated in shake flasks experiments using OPF juice as the sole carbon source. The highest P(3HB) content was recorded at pH 7.0, agitation speed of 220 rpm, and (NH4)2SO4 concentration at 0.5 g/L. By culturing the wild-type strain of C. necator under the aforementioned conditions, the cell dry weight (CDW) and P(3HB) content obtained were 9.31 ±0.13 g/L and 45 ±1.5 wt.%, respectively. This accounted for 40% increment of P(3HB) content compared to the nonoptimized condition. In the meanwhile, the effect of dissolved oxygen tension (DOT) on P(3HB) production was investigated in a 2-L bioreactor. Highest CDW (11.37 g/L) and P(3HB) content (44 wt.%) were achieved when DOT level was set at 30%. P(3HB) produced from OPF juice had a tensile strength of 40 MPa and elongation at break of 8% demonstrated that P(3HB) produced from renewable and cheap carbon source is comparable to those produced from commercial substrate.